algebra confused simple question

bronx.system

Junior Member
Joined
Apr 5, 2013
Messages
56
Im having trouble with the worded questions eg

One number is 13 less than the other. Their sum is 45. What are the numbers?

My working
i have been messing around with numbers and not sure why this works can someone please just explain each step please

m + ( m - 13) = 45
2m - 13 = 45 (this part makes me think i wrote it wrong because the above means it should be 2m - 13m = 45?)
2m = 58
m = 29

then i just subtract 29 from 45 and get 16
29 + m = 45
m = 16

so numbers are 16, 29
i checked answer but im sure my working is flawed can someone point out where ><
 
Last edited:
Im having trouble with the worded questions eg

One number is 13 less than the other. Their sum is 45. What are the numbers?

My working
i have been messing around with numbers and not sure why this works can someone please just explain each step please

Let the larger # = m

m + ( m - 13) = 45
2m - 13 = 45 ....................................This is correct

(shouldnt it be 2m + 13m = 45)? ....................this question makes me nervous! How do you think m + (m-13) = 45 becomes 2m + 13m = 45?

It is very important to understand how
m + (m - 13) becomes 2m - 13.
2m = 58
m = 29

then i just subtract 29 from 45 and get 16
29 + m = 45
m = 16

so numbers are 16, 29

is my working out correct?

Correct - except the comments above.

You can verify your answer by checking the given conditions.

One number is 13 less than the other. 29 - 16 = 13 ................................Checks

Their sum is 45. 29 + 16 = 45 ..............................................................Checks

Since it satisfes the given conditions, your answers are ost probably correct.
 
.
m = number 1
n = number 2, which is 13 less than number 1, so it is (m-13)


2m - 13 = 45 (this part makes me think i wrote it wrong because the above means it should be 2m - 13m = 45?)

This is correct. That is a simple addition.
If you multiply them it would be
:
m*(m-13)= m*m-13*m = m2-13m
if you add them it is:
m+(m-13) = m+m-13 = 2m-13


then i just subtract 29 from 45 and get 16
29 + m = 45
m = 16

or: n = m-13 = 29-13 =16
and 29+16=45
so that's the proof that it is correct

so numbers are 16, 29
i checked answer but im sure my working is flawed can someone point out where ><
 
Last edited:
thanks for reply

i think i understand now

m + ( m - 13) = 45
EDIT:

thanks thats what i was confused about

the parentheses confused me i thought i had to multiple :mrgreen:

all good thanks all
 
Last edited:
Top